Causal Framing of The Sumatra Floods in The Jakarta Post - Dang Hartono; Stefanus Angga Badara Prima (ITScience (Information Technology and Science), 2026)
This study examines media framing and responsibility attribution in The Jakarta Post’s early disaster communication regarding the 2025 Sumatra floods. A corpus consisting of 29 articles published between 28 November and 10 December 2025 was analysed. The methodology combined prominence coding with critical discourse analysis. Initially, each headline and the first 50 words of the article body were coded to identify the most prominent causal explanation. Next, full texts were coded for anthropogenic-cause claims, source types, metaphors, agentless passives, and nominalisations. Fifteen articles (51.7%) foregrounded meteorological causation, two (6.9%) foregrounded anthropogenic causation, and twelve (41.4%) provided no explicit causal frame in the headline or lead. Five articles (17.2%) contained a body-level anthropogenic-cause claim under the conservative coding rule. Government sources appeared in 28 articles (96.6%), expert or scientific sources in 19 (65.5%), and NGO sources in 5 (17.2%). Agentless passives occurred in 27 articles (93.1%) and nominalizations in 25 (86.2%). The findings show that early media framing made weather and official information more textually prominent than land-use and corporate drivers, although anthropogenic explanations entered some later reports. The study contributes a replicable procedure for examining how prominence, sourcing, and grammar organise disaster causation without assuming audience effects.